Relation of Red Cell Distribution Width With Presence and Severity of Coronary Artery Ectasia - Isik, Turgay; Kurt, Mustafa; Ayhan, Erkan; Uyarel, Huseyin; Tanboga, Ibrahim Halil; Korkmaz, Ali Fuat; Kaya, Ahmet; KAYA, AHMET; Sevimli, Serdar (My University, 2012)
Red cell distribution width (RDW) is an index that has been shown to be an independent correlate of adverse outcomes in some cardiac conditions. Isolated coronary artery ectasia (CAE) is an abnormality of the coronary anatomy and can cause ischemia. We hypothesized that increased RDW would be associated with isolated CAE because both are associated with inflammation. In this study, 2345 patients who received coronary angiography were retrospectively evaluated. After exclusion, 75 patients with isolated CAE and 96 consecutive patients with normal coronary were included in the study. The severity of isolated CAE was determined according to the Markis classification. Baseline RDW was measured as part of the automated complete blood count. Red cell distribution width was observed to be an independent predictor of both presence and severity of isolated CAE. In conclusion, RDW is associated with both the presence and severity of isolated CAE.
Keywords: Coronary Artery Ectasia